Human Embryonic Stem Cells as a Model for Hematopoietic Stem Cell Differentiation and Viral Infection. Issue 12 (15th December 2022) - Crawford, Lindsey B.
Abstract: Pluripotent human embryonic stem cell (hESC) lines are a valuable in vitro tool to differentiate specific cell lineages, including cells from all three germ layers, i.e., neuronal cells, myocytes, and hematopoietic cells, including progenitors (described here), lymphoid cells, and myeloid cells. However, dramatically different cell subtypes and functional properties of specific cells can arise depending on the differentiation technique used. We previously optimized hematopoietic stem cell differentiation from two different NIH‐approved hESC lines to generate CD34 + hematopoietic progenitor cells (HPCs). Infection of these HPCs with a common herpesvirus (human cytomegalovirus) results in maintenance of viral latency, capability of viral reactivation, recapitulation of viral mutant phenotypes, and virus‐induced myelosuppression of hematopoietic differentiation. However, different HPC subpopulations support different viral latency and reactivation phenotypes, and different hESC‐to‐HPC differentiation methods alter the ratio of stem cell subsets. In addition, differences in differentiation methods are dependent on both protocol/reagents and user techniques. Here, we report a simplified and optimized method to generate large numbers of CD34 + HPCs with consistent phenotypes and demonstrate a comparison of several common methods that can be used to control the ratio of available HPC subpopulations. A key aspect of this approach is that we achieve consistency in differentiation across users in different laboratories and, importantly, among newly trained individuals. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Maintenance of human embryonic stem cells (hESCs) Basic Protocol 2 : Differentiation of hESCs to hematopoietic progenitor cells (HPCs) Basic Protocol 3 : Downstream functional differentiation of hESC‐derived HPCs to mature lineages Support Protocol 1 : Freezing and testing frozen batches of hESCs Support Protocol 2 : Counting hESCs Support Protocol 3 : Phenotyping by flow cytometry